PENGARUH STRATEGI BERSAING DAN MANAJEMEN RANTAI PASOKAN TERHADAP KINERJA PERUSAHAAN (STUDI PADA PT PACKET SYSTEMS INDONESIA) - Rahmaini Rahmaini; Siska Warastuti (Universitas Prof. Dr. Moestopo (Beragama), 2021)
This study aims to determine and analyze the effect of competitive strategy and supply chain management on company performance at PT Packet Systems Indonesia. The research method used is a quantitative method. Data collection techniques using questionnaires and literature study. The sampling technique uses the Slovin method with a sample of 77 respondents taken from all employees at PT Packet Systems Indonesia. Data analysis techniques using regression analysis and correlation using SPSS ver 25 as an analysis tool. Based on the results of the study showed that the competitive strategy has a positive influence and is at a fairly strong level on company performance that is equal to 34.3%. While supply chain management has a positive influence and is at a strong level on company performance that is equal to 62.1%.